1997
DOI: 10.1002/(sici)1097-0215(19971127)73:5<757::aid-ijc24>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Fas (CD95) in human p53wild-type cancer cells treated with ionizing radiation

Abstract: Fas is a cell‐surface protein which belongs to the tumor‐necrosis‐factor‐receptor family. Signals through Fas are able to induce apoptosis in sensitive cells, and thus modalities for regulating the level of Fas expression on tumor cells are needed. We have studied cellular responses to gamma irradiation. The level of p53 tumor‐suppressor protein was found to be elevated 3 hr after irradiation of p53wild‐type MCF‐7 breast‐carcinoma cells. Interestingly, accumulation of p53 was followed by up‐regulation of surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
72
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(74 citation statements)
references
References 15 publications
0
72
1
Order By: Relevance
“…39 Radiotherapy up-regulates Fas in human p53 wt cancer cells. 40 Therefore, combined induction of p53 and FL is a good candidate for enhancing the therapeutic effect of chemotherapy as well as radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…39 Radiotherapy up-regulates Fas in human p53 wt cancer cells. 40 Therefore, combined induction of p53 and FL is a good candidate for enhancing the therapeutic effect of chemotherapy as well as radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…This down-regulation of Fas in advanced sun damage may represent the loss of proliferation control allowing for uncontrolled growth. Experimental data of Scheard et al 21 strongly indicated that Fas upregulation in cells treated with ionizing radiation is dependent on wild-type p53 activity. Fas overexpression coincides with G 1 cell cycle arrest, which is a known postirradiation p53-dependent phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Due to limits in toxicity, some tumor cells within a given tumor mass may receive a sublethal dose of radiation. This dose, however, may be capable of modulating numerous classes of genes, resulting in phenotypic alteration of the tumor cells [4][5][6]. Genes that have been shown to be up-regulated postirradiation in murine and/or human tumors include Fas, MHC class I, ICAM-1, and multiple TAAs.…”
Section: Vaccine and Radiationmentioning
confidence: 99%